2019
DOI: 10.2135/cropsci2018.11.0707
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Cool‐Season Turfgrass Response with Solvita Soil Tests, Part 2: CO2–Burst Carbon Concentrations

Abstract: Current turfgrass fertilizer recommendations do not account for plant‐available soil N mineralized from labile C fractions. The Solvita Soil CO2–Burst (SSCB) test can measure mineralizable C via soil CO2 respiration. This study was conducted across 3 yr (2014–2016) in Connecticut to determine: (i) if SSCB–C concentrations are correlated to responses from predominately Kentucky bluegrass (Poa pratensis L.) and tall fescue [Schedonorus arundinaceus (Schreb.) Dumort.] lawns, and (ii) the probability of turfgrass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 48 publications
6
12
1
Order By: Relevance
“…The lack of strong and consistent response of Nmin could also be attributed to its estimation from biological indicators in HSHT (Solvita CO 2 -C, WEOC, and WEON), which also showed a generally poor response to management differences (Tables 2-4). Other studies also reported a lack of strong response of Nmin estimated from HSHT parameters to agromanagement practices (Castro Bustamante & Hartz, 2016;Dick & Culman, 2016;Tu, 2016;Moore, Guillard, Morris, & Brinton, 2019). In addition, some studies discussed the limited applicability of using Nmin in predicting crop N fertilizer requirement due to the requirement of advanced yield estimation, high measurement variability of HSHT indicators, and region-specific calibration and validation of such pre-dictions (Norris, Chim, Evanylo, Reiter, & Thomason, 2018;Stahl, Fernández, & Kaiser, 2016).…”
Section: Potential Nitrogen Mineralization Ratesmentioning
confidence: 99%
“…The lack of strong and consistent response of Nmin could also be attributed to its estimation from biological indicators in HSHT (Solvita CO 2 -C, WEOC, and WEON), which also showed a generally poor response to management differences (Tables 2-4). Other studies also reported a lack of strong response of Nmin estimated from HSHT parameters to agromanagement practices (Castro Bustamante & Hartz, 2016;Dick & Culman, 2016;Tu, 2016;Moore, Guillard, Morris, & Brinton, 2019). In addition, some studies discussed the limited applicability of using Nmin in predicting crop N fertilizer requirement due to the requirement of advanced yield estimation, high measurement variability of HSHT indicators, and region-specific calibration and validation of such pre-dictions (Norris, Chim, Evanylo, Reiter, & Thomason, 2018;Stahl, Fernández, & Kaiser, 2016).…”
Section: Potential Nitrogen Mineralization Ratesmentioning
confidence: 99%
“…(2019a) reported that PMC increased with increasing N rates. The varying results in PMC response to N fertilizer may be a result of N rates, in which higher N (100–257 kg N ha −1 ) amounts decrease PMC, whereas small N (12.5–50 kg N ha −1 ) additions may increase PMC (Grandy et al., 2013; Moore et al., 2019b). There was a nonsignificant trend for treatments with higher PMC to exhibit better turfgrass quality.…”
Section: Resultsmentioning
confidence: 99%
“…Potentially mineralizable N (PMN) is the inorganic N released during the incubation (Franzluebbers et al., 2018; McDaniel & Grandy, 2016). Both PMC and PMN can be an indicator of soil N‐supplying power, as has been shown with maize and turfgrass N response studies in the United States (Franzluebbers et al., 2018; McDaniel et al., 2020; Moore et al., 2019, 2019ab; Yost et al., 2018).…”
Section: Introductionmentioning
confidence: 81%
“…The SI measurements provide an objective measure of plant‐N status for turfgrass lawns, whereas the current practice of using predetermined N rates do not. A routine fall application of N at the currently recommended rates without adjusting for plant‐N status before fertilization will most likely increase the chance of excess N and increase leaching losses especially when soil mineralization potential is high (Miltner, Stahnke, & Backman, 2001; Moore et al., 2019; Yao et al., 2009) and/or if there is N carryover from previous fertilizer applications (Waddington et al., 1976). Therefore, measuring the reflectance SI of cool‐season turfgrasses during the fall to determine plant‐N status should provide more accurate guidance for N fertilization and protection against excess fertilizer N applications.…”
Section: Discussionmentioning
confidence: 99%
“…A commonly used spectral measurement in turfgrass research to determine treatment differences is the normalized difference vegetative index (NDVI). There are numerous citations in the turfgrass literature reporting significant relationships between NDVI or other spectral‐reflectance signals with N fertilization (reviewed in Bell, Kruse, & Krum, 2013; Catureglia et al., 2015, 2016; Caturegli et al., 2020; Geng, Guillard, Mangiafico, & Morris, 2014; Geng, Guillard, & Morris, 2014; Guillard, Fitzpatrick, & Burdett, 2016; Inguagiato & Guillard, 2016; Moore et al., 2019; Moore, Guillard, Morris, & Brinton, 2019; Obear, Kreuser, Hubbard, DeBels, & Soldat, 2017). However, relationships between reflectance signals and the response of turfgrass to N fertilization have not been analyzed with the objective to create site‐specific fertilizer recommendations.…”
Section: Introductionmentioning
confidence: 99%